2020
DOI: 10.1186/s12957-020-01821-y
|View full text |Cite
|
Sign up to set email alerts
|

Is subtotal gastrectomy feasible for the treatment of gastric stump cancer located at the anastomotic site after distal gastrectomy for benign lesions?

Abstract: Background: Total gastrectomy (TG) is a widely accepted procedure for treating gastric stump cancer (GSC). However, subtotal gastrectomy (SG) would benefit elective patients with GSC. The aim of this study was to clarify the safety and long-term prognosis of SG in treating GSC after distal gastrectomy for benign lesions. Methods: A total of 53 patients with GSC located at the anastomotic site or gastric body between May 1999 and December 2018 at our hospital were included. In total, 21 patients underwent SG, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…TG is a widely accepted approach for treating GRC. Ma et al [ 13 ] reported that SG was a suitable alternative surgical procedure for GRC located at the anastomotic site after distal gastrectomy for benign diseases. Of 45 patients, 21 patients underwent SG with lymph node dissection.…”
Section: Discussionsupporting
confidence: 91%
“…TG is a widely accepted approach for treating GRC. Ma et al [ 13 ] reported that SG was a suitable alternative surgical procedure for GRC located at the anastomotic site after distal gastrectomy for benign diseases. Of 45 patients, 21 patients underwent SG with lymph node dissection.…”
Section: Discussionsupporting
confidence: 91%